277 Diagnosing Kingella Kingae Osteoarticular Infections in Young Children via Specific Oropharayngeal Swab PCR. (October 2012) - Anderson, R; Dubois-Ferrière, V; Cherkaoui, A; Schrenzel, J; Ceroni, D
Abstract : Background: Diagnosing osteoarticular infections (OAI) caused by the increasingly recognized pathogen, K. Kingae, in young children remains challenging. The purpose of this study was to investigate whether specific oropharyngeal swab PCR could predict K. Kingae OAI in this population . Methods: A total of 123 children aged 6 to 48 months, presenting atraumatic osteoarticular complaints were prospectively enrolled. All were clinically evaluated, underwent hematologic and radiological investigations. Blood and oropharayngeal swab samples were tested with a K. kingae specific PCR assay. OAI was defined as the presence of pathogenic bacteria in bone, joint or blood samples, or magnetic resonance imaging consistent with infection despite negative microbiology. Positive culture or PCR for K. kingae in blood, bone or synovial fluid confirmed OAI due to this pathogen. Results: Forty children met the OAI case definition; 30 had K. kingae OAI, one had OAI du to another organism, and 9 had no microbiologic diagnosis. All 30 oropharyngeal swabs from the patients with K. kingae OAI, and 8 swabs from the 84 patients without OAI or with OAI caused by another organism, were positive. The sensitivity and specificity of oropharyngeal swab PCR for K. kingae OAI were 100% and 90.5%, respectively; positive and negative predictive values were 78.9%, and 100%, respectively. Conclusions: Detection of K. kingae DNA in oropharayngeal swabs from children presenting clinical findings of OAI is highly predictive for K. kingae OAI. This test represents thus a valuable diagnostic tool, which could improve the recognition of OAI in young children.